2021
DOI: 10.1371/journal.pone.0255269
|View full text |Cite
|
Sign up to set email alerts
|

A new Multi Sine-Cosine algorithm for unconstrained optimization problems

Abstract: The Sine-Cosine algorithm (SCA) is a population-based metaheuristic algorithm utilizing sine and cosine functions to perform search. To enable the search process, SCA incorporates several search parameters. But sometimes, these parameters make the search in SCA vulnerable to local minima/maxima. To overcome this problem, a new Multi Sine-Cosine algorithm (MSCA) is proposed in this paper. MSCA utilizes multiple swarm clusters to diversify & intensify the search in-order to avoid the local minima/maxima prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…The results indicated the method’s efficacy in exploring and exploiting the search space, selecting the fewest feature subset possible, reducing datasets’ dimensions, and improving a high classification rate with low run-time on all datasets used. Moreover, Rehman et al [ 202 ] developed a novel Multi Sine Cosine algorithm (MSCA), which employed several swarm clusters to explore & exploit the search space to evade the local minima or maxima issues. The researchers evaluated the hybridization performance on different benchmark functions.…”
Section: Metaheuristic Algorithms For Multiclass Feature Selectionmentioning
confidence: 99%
“…The results indicated the method’s efficacy in exploring and exploiting the search space, selecting the fewest feature subset possible, reducing datasets’ dimensions, and improving a high classification rate with low run-time on all datasets used. Moreover, Rehman et al [ 202 ] developed a novel Multi Sine Cosine algorithm (MSCA), which employed several swarm clusters to explore & exploit the search space to evade the local minima or maxima issues. The researchers evaluated the hybridization performance on different benchmark functions.…”
Section: Metaheuristic Algorithms For Multiclass Feature Selectionmentioning
confidence: 99%
“…The analysis of Table 4 shows that TN prediction activated carbon based on VELM inMAE = 5:04 mg/dm 3 and SCA inMAE = 8:17 mg/dm 3 , and fusion of VELM-SCA givesMAE = 4:23 mg/dm 3 , similar for MAPE and VELM inMAPE = 99:67 mg/dm 3 , and SCA inMAPE = 11:54 mg/d m 3 and hybrid of VELM-SCA givesMAPE = 8:45 mg/dm 3 . In addition, TP prediction activated carbon based on VELM inMAE = 1:31 mg/dm 3 and SCA inMAE = 2:61 mg/dm 3 , and hybrid of VELM-SCA givesMAE = 1:45 mg/dm 3 , similar for MAPE and VELM inMAPE = 12:77 mg/dm 3 and SCA inMAPE = 17:77 mg/dm 3 , and hybrid of VELM-SCA givesMAPE = 12:76 mg/dm 3 . Prediction of wastewater quality requires parametric indicators of TN, and TP shown that our proposed work VELM-SCA gives better performance.…”
Section: Root Mean Square Error (Rmse)mentioning
confidence: 93%
“…To improve the accuracy rate, this voting approach is used [2]. For improving the exploitation sine-cosine, the algorithm (SCA) allows to select the prediction of carbon by using search operations in a mathematical function of the sine and cosine [3].…”
Section: Introductionmentioning
confidence: 99%
“…Rehman et al [36] proposed a Multi Sine-Cosine algorithm in which multiple swarm clusters are utilized for diversification and intensification of the search space to avoid the local optima problem. This modified SCA was tested on benchmark numerical functions, and it performed better than basic SCA.…”
Section: Related Workmentioning
confidence: 99%